Innovation and export portfolios - Klinger, Bailey (Policy research working paper, 2006)
"This paper examines the link between sectoral concentration and overall performance in the search for on-the-frontier innovations, inside-the-frontier innovations, and export booms. It extends the literature by increasing country coverage and the types of search processes considered, and by focusing on the links with overall performance in these search processes. After controlling for the necessary relationships as well as fixed effects at the country/commodity group level, the paper finds a clear negative relationship between the concentration of innovation portfolios and performance: countries that are the most successful in these search processes have their successes spread across a broader range of industries than those with poorer performance. Furthermore, the search for export booms exhibits the least amount of sectoral concentration and path-dependence. These findings suggest that public support for these processes need not be focused in a narrow range of sectors, and modeling of these processes in theoretical work, particularly in the search for export booms, should be of a stochastic flavor. "--World Bank web site